Kode Dan Alih Kode Dalam Wacana Siaran Radio FM Di Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
This paper describes the phenomenon of code-switching as found in the discourse of informal and interactive FM radio programs in Yogyakarta. It was found that the announcers frequently employ different codes, such as Indonesian and Javanese in their broadcasting. In addition, this study also shows that the code switching is caused by several factors, such as (a) uncertain relation of speakers, (b) the influence of the other's preceding utterance, (c) the influence of speech situation, (d) the influence of topics, (e) the arrival of